Numerical simulation study of oil–water separation based on a super-hydrophilic copper net - Bai, Kun; Liu, Weinan; Zhao, Maoyu; Li, Kaifang; Tian, Yiming (Frontiers in Environmental Science, 2022)
Green and environment-friendly oil-water separation is an important technique of reducing the environmental pollution. In this study, the oil-water separation effect of the super-hydrophilic copper net was optimized through numerical simulation and orthogonal experiments. To be specific, a super-hydrophilic copper net was prepared using the solution etching method to perform oil-water separation experiments, and a favorable oil-water separation effect was achieved. First, the influences of oil-water flow velocity, copper net mesh size, and surface wettability on the oil-water separation effect of the super-hydrophilic copper net were explored via single-factor experiments. The results showed that the oil resistance of the super-hydrophilic copper net degraded and its oil-water separation effect became poor due to the increasing oil-water flow velocity, enlarged copper net mesh size and reduced oil contact angle on the surface of the super-hydrophilic copper net. On this basis, the optimized oil-water separation parameters were obtained through orthogonal experiments. It could be known that the oil-water separation effect was influenced by oil-water flow velocity, oil contact angle, and copper net mesh size. Furthermore, the copper net was etched using sodium hydroxide and sodium persulfate mixed solution to prepare a 500-mesh super-hydrophilic copper net for the oil-water separation experiment. The optimized process parameters were as follows: velocity=0.1 m/s, copper net mesh size=30 µm, oil contact angle=150º, and oil removal rate=96.4%. The study results provide a theoretical basis, method and means for the practical application of super-hydrophilic copper nets.